Liver and spleen elastography of dogs affected by brachycephalic obstructive airway syndrome and its correlation with clinical biomarkers - Facin, Andréia Coutinho [UNESP]; Uscategui, Ricardo Andres Ramirez; Maronezi, Marjury Cristina [UNESP]; Pavan, Letícia [UNESP]; Menezes, Mareliza Possa [UNESP]; Montanhim, Gabriel Luiz [UNESP]; Camacho, Aparecido Antonio [UNESP]; Feliciano, Marcus Antônio Rossi; Moraes, Paola Castro [UNESP] (Springer Nature, 2020)
The purpose of this study is to determine whether the brachycephalic obstructive airway syndrome (BOAS) is correlated to alterations in liver and spleen elasticity. Forty-eight brachycephalic and 22 mesocephalic dogs were submitted to a BOAS functional assessment, laboratory tests, abdominal ultrasound and liver and spleen Acoustic Radiation Force Impulse (ARFI) elastography. Dogs clinically affected by BOAS had higher values of liver stiffness (p < 0.001) than healthy dogs: medial lobes (1.57 ± 0.37 m/s), left and right lateral lobes (1.54 ± 0.50 m/s, 1.23 ± 0.28 m/s, respectively) and caudate lobe (1.28 ± 0.42 m/s). Compared to the mesocephalic group, the brachycephalic group (BOAS clinically affected and unaffected dogs) had higher spleen (2.51 ± 0.45 m/s; p < 0.001) and liver stiffness (p < 0.001): medial lobes (1.53 ± 0.37 m/s), left and right lateral lobes (1.47 ± 0.47 m/s, 1.20 ± 0.30 m/s, respectively) and caudate lobe (1.23 ± 0.40 m/s). Principal component analysis explained 70% of the variances composed by liver stiffness increase, erythrocytes and alanine aminotransferase reduction. Brachycephalic dogs had higher spleen and liver stiffness and a subacute inflammatory state, which represent another BOAS systemic effect. Consequently, these dogs can be at higher risk of hepatic disorders compared with mesocephalic dogs, similarly to humans affected by sleep apnea syndrome.